Factors that influence the willingness to recommend magical towns of the Mexican northwest - Ibáñez-Pérez, Reyna María; Olmos-Martínez, Elizabeth; Almendarez-Hernández, Marco Antonio (Acta Universitaria, 2022)
The recommendation of a tourist destination is a key factor to increase the influx of visitors. The objective of this study is to estimate the impact of the factors that influence the willingness to recommend of tourists in four Magical Towns (PM, from its Spanish acronym), based on their own experience, since there are only descriptive works and not with an econometric approach. The theoretical framework used to analyze the regressors that are related to the response variable is based on random utility maximization. The estimated logit and probit models explain that national visitors; individuals between 49 and 55 years old; those who paid for an excursion service; and people who rated as excellent the restaurant service, recreational and leisure activities, natural attractions and cultural reasons, as well as the historical reason influence on a greater probability to recommend the sites. This research contributes with scientific knowledge and information for tourism managers in Mexico.